Dynamic interdependence between volatility of Shariah stock and bond - Shari, Aminah; Mahat, Fauziah; Ab Razak, Nazrul Hisyam; Yahya, Mohamed Hisham (Human Resource Management Academic Research Society, 2023)
The purpose of this research is to investigate the correlation between bond yields and the Shariah equity index from 2007 to 2019. The Multivariate-GARCH Dynamic Conditional Correlation (DCC) model is applied to the daily data indices of five bond markets, namely conventional bond, corporate bond, corporate sukuk, government bond, and government sukuk, as well as the daily index of the Islamic equity market, which is represented by FTSE Bursa Malaysia EMAS Shariah. The empirical evidence reveals a substantial correlation between these sharia stock and sukuk indexes, demonstrating that investors' risk tolerance fluctuates over time. Co-movement power fluctuates throughout time, and the government bond is dominant.